Transformacja i rekonstrukcja tożsamości narodowej polskich imigrantów w Norwegii - Pawlak, Marek (My University, 2012)
Celem pracy jest próba zanalizowania „problemu”, a więc narodowości, oraz procesów towarzyszących transformowaniu i rekonstruowaniu „polskości” w oparciu o kontekst życia „tam” (w Norwegii) i „tu” (w Polsce). Głównym przedmiotem mojej analizy jest tym samym „tożsamość” oraz jej strategiczność, sytuacyjność i relacyjność w życiu migrantów. Tego typu perspektywa pociąga za sobą szereg problematycznych (aczkolwiek niezmiernie istotnych) kwestii dotyczących wpływu szerokiego kontekstu współczesności na lokalnie wytwarzane praktyki identyfikacyjne. Migracje, globalizacja i transnarodowość – stanowiąc jedne z podstawowych aspektów dzisiejszego świata – generują pewnego rodzaju „gramatykę” współczesności. W konsekwencji, tożsamość osadzona zostaje w ramach dialektycznego procesu podobieństwa i różnicy. Z jednej bowiem strony, doświadczanie globalnych powiązań i przepływów prowadzi do „wykorzenienia” tożsamości z ograniczonych lokalnie przestrzeni; z drugiej natomiast – samo „wykorzenienie” prowadzi do powstawania mechanizmów „ponownego zakorzenienia”, jako że człowiek potrzebuje pewnej ciągłości narracji życiowej i identyfikacji. Tożsamość migranta staje się wówczas strategią radzenia sobie w sytuacji diasporycznej, będąc przy tym zależną od selektywnie doświadczanych ideologii (kapitalizm, nacjonalizm, kosmopolityzm) oraz codziennych (intymnych) lojalności i przynależności (uwarunkowania socjo-ekonomiczne).

The primary question of my doctoral dissertation concerns the subject matter of national identity in the context of contemporary world and global migration. In particular, I am interested in the phenomena that reveal processes of identity politics among Polish economic immigrants living and working in Norway. Therefore, the detailed questions raised in my thesis involve the immigrants’ transformation and reconstruction of such categories as nationality (or ethnicity), the ‘global’ and the ‘local’, as well as, the immigrants’ perception of mobility and transnational connections. Additionally, I also analyse the complex issue of how the state and national ideologies function in the contemporary – to use Ulf Hannerz’s term – ‘global cultural flow chart’. In other words, what does it mean to be ‘national’ nowadays? How do we become ‘national’ entities? Are we experiencing a sort of erosion of national identities due to the heightened mobility and global flows; or perhaps it is just the opposite – precisely because of the constant movement of different nationalities and ethnicities we may observe a general revival of national identities? . These questions are, however, supplemented by additional contexts of immigrants’ identification processes, which involve an array of many other allegiances than merely the ‘national’ ones. Although, national belonging seems to play a lucid and pivotal role in the context of contemporary mobility, it usually depends on the different socio-cultural categories, such as social class, gender, etc. After all, national identity does not appear in a social vacuum – individuals construct and transform this category based on their own personal experiences and loyalties. Therefore, the crucial analysis of migrants’ identity constructions emphases the strategic, contextual and pragmatic ‘use’ of national categories while dealing with various problems and opportunities in diasporic situations. This sort of process may be described as a ‘shifting’ from national to focal and situational factors of identity, which are significant in migrants transnational practices and social fields.
Transformation and reconstruction of national identity among polish immigrants in Norway
Wydział Historyczny: Instytut Etnologii I Antropologii Kulturowej
Keywords: Migracje; Migration; Tożsamość narodowa; National identity; Transnarodowe powiązania; Transnationalism; Transnarodowy habitus; Transnational habitus